State of the art: pregnancy in spinal muscular atrophy in the treatment era - Walter, Maggie C.; Günther, Bernert; Blaschek, Astrid; Deschauer, Marcus; Günther, René; Hiebeler, Miriam; Hahn, Andreas; Kamm, Christoph; Kirschner, Janbernd; Lochmüller, Hanns; Löscher, Wolfgang; Müller-Felber, Wolfgang; et al. (Journal of neuromuscular diseases, 2025)
An increasing number of adults with spinal muscular atrophy (SMA) wish to become parents. New disease-modifying therapies (DMT) have improved health outcomes and are expected to reduce disability in adults with SMA, but their current label prevents their use in pregnancy. While there is some information on pregnancy outcomes in the pre-DMT era, little has been published recently, and no ubiquitously accepted guidelines exist. Nonetheless, it is crucial to provide knowledgeable and open counselling, ideally in the context of treatments. Counseling for both adolescent and adult patients should include the subject of ‘reproductive choices’ when discussing the selection of DMTs for those considering parenthood. A multi-disciplinary team, including gynecologists and neurologists with expertise in neuromuscular disorders must closely monitor pregnant patients with SMA, preferably within disease registries, to detect potential complications early and ensure optimal treatment options are available. Real-world data in so far three patients with SMA showed a beneficial pregnancy outcome with nusinersen. It is anticipated that forthcoming real-world data will finally clarify the safety of administering Nusinersen during pregnancy, particularly in relation to child health and for preserving muscle function and preventing motor deterioration in the affected mother.